Combination of diclofenac plus somatostatin in the prevention of post-ERCP pancreatitis: a randomized, double-blind, placebo-controlled trial - Katsinelos, P.; Fasoulas, K.; Paroutoglou, G.; Chatzimavroudis, G.; Beltsis, A.; Terzoudis, S.; Katsinelos, T.; Dimou, E.; Zavos, C.; Kaltsa, A.; Kountouras, J. (Endoscopy, 2012)
Background and study aims: Pancreatitis is the most common complication of therapeutic endoscopic retrograde cholangiopancreatography (ERCP), and many pharmacoprophylactic approaches have been suggested, though not without controversy. The aim was to investigate the impact of combined therapy with diclofenac plus somatostatin on reducing the frequency and severity of post-ERCP pancreatitis (PEP).Patients and methods: A prospective, double-blind, placebo-controlled trial was conducted in two tertiary referral centers, with 540 eligible patients randomized to receive either combined therapy with diclofenac 100 mg rectally 30 to 60 minutes before ERCP plus somatostatin 0.25 mg/h for 6 hours (group A), or a placebo suppository identical in appearance to the diclofenac along with saline solution (group B). Patients were clinically evaluated and serum amylase levels were determined before ERCP and at 6 and 24 hours post-procedure. Standardized criteria were used to diagnose and grade the severity of PEP. Adverse events were recorded prospectively.Results: There were no statistical differences between the groups regarding demographic data, ERCP findings, and procedure risk factors for PEP. The overall incidence of acute pancreatitis was 7.2 %. The PEP rate was significantly lower in the patients who received the combination therapy than in controls (4.7 % vs. 10.4 %, P = 0.015). Previous history of acute pancreatitis (P = 0.001), pancreatic opacification of first-class branches and beyond (P = 0.008), and absence of pharmacoprophylaxis (P = 0.023) were identified as independent risk factors for PEP in multivariate analysis.Conclusion: Although combined prophylactic therapy with diclofenac plus somatostatin was promising in reducing frequency of PEP, further comparative large-scale studies are needed to confirm our findings before definitive conclusions can be drawn.